PENGARUH MEDIA WAYANG SUKURAGA TERHADAP KETERAMPILAN MENULIS DESKRIPSI PADA SISWA KELAS TINGGI SEKOLAH DASAR - Nawaliyatul Hilwa; Iis Nurasiah; Dyah Lyesmaya (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to determine the effect of the Sukuraga puppet media on students’ descriptive writing skills in upper classes of elementary school. The type of research was Quasi-Experimental design with a Nonequivalent Control Group Design. The population of this research was the fifth-grade students of Madrasah Ibtidaiyah Rambay in the 2020/2021 academic year. The samples were determined by saturated sampling. The samples of this study were 20 students from class V B as the experimental group and 20 students from class V A as the control group. The descriptive writing skills research data resulted from the instrument in the form of a test that explained one thing that had been validated. Data of the skills described the analysis by using a two-sample independent T test. The test results produced a sig value of 0.025, smaller than 0.05. Thus, H₀ was rejected, H₁ was accepted. These results indicated significant differences between the experimental class and the control class. The Sukuraga puppet media affected students' descriptive writing skills.